Shifting Fortunes and Enduring Poverty in Madagascar : Recent Findings - Osborne, Theresa (Washington, DC: World Bank, 2017)
Madagascar remains among the poorest countries in the world, and has shown little improvement in indicators of the well-being of its population over recent years. The economy faces an array of challenges in reducing poverty, including an unfavorable investment climate, severe infrastructure deficits, and political instability. This report synthesizes the insights obtained from a series of five papers on poverty, inequality, labor markets, and returns to agricultural and nonfarm enterprises in Madagascar over the period 2001-12. These papers draw on a combination of empirical techniques, household living standards data, and firm-level data to elucidate key dynamics and structural issues driving poverty and welfare (in all cases measured as per capita consumption) over this dozen-year period.